A standard method for predicting conservation status from herbarium specimens in the context of a new phylogeny and taxonomy of Loudetia - Kamundi, Dickson Athanasius (My University, 2008)
LAYOUT: A general introduction of issues covered in chapters 2-5 and a review of literature, including the taxonomic and conservation status of Loudetia species, morphometric and phylogenetic methods, is presented under general introduction in Chapter 1. Chapter 2 contain a taxonomic clarification of the Loudetia simplex complex. Chapter 3 covers a phylogenetic hypothesis of species of Loudetia and Loudetiopsis, including an investigation of the determination of discrete character states from quantitative characters and an updated classification of Loudetia. Chapter 4 presents an updated enumeration of species of Loudetia. A new method of predicting risk in species using herbarium specimens is presented in Chapter 5. Findings of this thesis are summarized in chapter 6: general discussion and conclusions.